(−)‐Epicatechin induces physiological cardiac growth by activation of the PI3K/Akt pathway in mice. Issue 2 (10th October 2016) - De los Santos, Sergio; García‐Pérez, Viridiana; Hernández‐Reséndiz, Sauri; Palma‐Flores, Carlos; González‐Gutiérrez, Carlos J.; Zazueta, Cecilia; Canto, Patricia; Coral‐Vázquez, Ramón M.
Abstract : (−)‐Epicatechin, an abundant flavanol of the cocoa plant, has cardioprotective effects. Here, it is found that mice administrated with this flavanol show a cardiac physiological growth by activation of the PI3K/Akt signaling pathway. Additionally, this growth is reversed by stopping the administration of the flavanol. Abstract : Scope: The flavanol (−)‐epicatechin (Epi) has cardioprotective effects and improves physical capacity in normal mice. In addition, Epi increases nitric oxide (NO) production by activation of both PI3K/Akt or Ca 2+ /CaMI/CaMKII (where Akt is protein kinase B; PI3K is phosphoinositide 3‐kinase; CaMI is calmodulin; CaMKII is Ca 2+ /calmodulin‐dependent protein kinase II) signaling pathways, which have been associated with physiological and pathological cardiac hypertrophy, respectively. Notwithstanding all this information, few studies have been carried out that aimed to determine the potential beneficial effects that Epi may have in normal heart. Methods and results: Mice were treated by oral gavage with the flavanol Epi. The treatment induced a significant increase in heart weight, size of the free walls, and size of the cardiac fibers. Also, no evidence of cardiac fibrosis was revealed. Furthermore, the phosphorylation level of PI3K/Akt/mTOR/p70S6K (where mTOR is mammalian target of rapamycin; p70S6K is ribosomal protein S6 kinase beta‐1) proteins was significantly higher in the heart of Epi‐treated animals. In contrast, a significantly decreased level of pathological cardiac hypertrophy markers atrial natriuretic peptide and brain natriuretic peptide was observed along with no modification in the level of β myosin heavy chain beta, calmodulin, and Ca 2+ /calmodulin‐dependent protein kinase II proteins. Hemodynamic parameters indicated an improvement in mechanical heart performance after Epi treatment. Interestingly, morphometric parameters were similar between treated and untreated mice after 4 wk without treatment. Conclusion: These findings indicate that Epi treatment induced physiological cardiac growth in healthy mice by activation of the PI3K/Akt pathway.